Sotah - Ragen, Naomi (SIFRI Ltd, 1992)
Set against the backdrop of Jerusalem's ancient rituals, Sotah is a contemporary story of sacred and profane love, and a young woman's struggle to reconcile tradition with freedom. Ninety three weeks on the best-seller list."Sotah introduces a family with three daughters approaching the age of marriage: Devorah, Dina and Chaya Leah. In the strict orthodoxy of their world, a "Sotah is a wife suspected of infidelity who can be tried by ordeal to prove she is guiltless. Which sister could be capable of such a thought, let alone the act? Into the pious world of strict chaperoning and modest clothing, where a married woman's hair must never be seen by a man other than her husband--insinuates this serpent suggestion of evil. Ragen's powerful tale of three sisters spins endless questions: Which one? Could she? Did she? What changes could come into this orderly world because of unthinking actions?
Keywords: Contemporary Women; Fiction; Jewish